The Level of Knowledge of Parkinson’s Disease among Nonprofessional Caregivers in a Movement Disorders Center in Turkey - Murat Gultekin; Ayse Caglar Sarılar; Ayten Ekinci; Gozde Erturk; Meral Mirza (Parkinson's Disease)
Introduction. Only a few studies have been conducted to determine the level of knowledge among caregivers about Parkinson’s disease (PD). The aim of the current study was to determine the knowledge of PD among caregivers at a movement disorder clinic in Turkey. Methods. We conducted a questionnaire based interview with the subjects in a tertiary care neurology facility in Turkey. The questions were divided into two parts covering the symptomatology and treatment of PD. A questionnaire consisting of 10 questions was applied to the subjects who had to mark the correct option in a stipulated time. Results. Eighty caregivers were included in the study. The caregivers’ mean age was 47.94 years (SD = 12.40). There were 47 female caregivers (58.8%). The most well-known question was that the number of drugs given to the patient may vary with time (76.3%), whereas “the benefit noted in the patient’s treatment decreases over time” was the least known question (11.3%). Discussion. This study is the first in our country and shows the necessity to increase the knowledge of PD among caregivers and the public. Education programs may have a positive role in imparting knowledge to the caregivers of PD patients.